PENINGKATAN KEPERCAYAAN DIRI MELALUI BIMBINGAN KELOMPOK DI PANTI ASUHAN AISYIYAH PUTRA BUKITTINGGI - Ayu Lestari; Syawaluddin Syawaluddin; Cilung Ardizon (CV. ADIBA AISHA AMIRA, 2023)
This research started from the fact that there were some children at the Aisyiyah Putra Bukittinggi Orphanage who were shy when communicating with the environment, especially with people they had just met, then there were some children who preferred to be alone in their room rather than hanging out with others, and also There are some children who are insecure about their status and children who are introverted. When asked, they prefer to avoid and answer briefly, so these children can be said to lack self-confidence. Researchers tried to apply group guidance to increase the self-confidence of children in the orphanage. This research aims to reduce feelings of inferiority and increase children's self-confidence. The method used in this research is pre-experiment, one group pre-test, post-test. The subjects in this research were children at the Aisyiyah Putra Bukittinggi Orphanage who lacked self-confidence based on the results of observations. The data analysis technique uses the Wilcoxon rank test. The instrument used in this research is a measurement scale in the form of a questionnaire. The results of the research were seen from the implementation of the pre-test and post-test with an increase in each child. Analysis of the Wilcoxon signed rank test shows that the value of 0.018 is lower than 0.05, so it can be concluded that there is an increase in self-confidence through group guidance at the Aisyiyah Putra Bukittinggi Orphanage.